World War I Through the Eyes of a Cavalryman: an Overview of the Diary Entries - Elena V. Fedotova (Publishing house "Sreda", 2021)
The work is devoted to the analysis of the field diaries of the participant of the First World War V.D. Efremov (1890-1978), a native of the Chuvash village of Ilyutkino, Staro-Maksimkinskaya volost, Chistopol district, Kazan province. The purpose of the research is to study the document in the context of historical events and introduce them into scientific use. The work is based on the author's field materials. The document is analyzed from a historical perspective. At the same time, in this work, the author turns to ethnographic and literary approaches. V.D. Efremov (1890-1978) - cavalryman of the 5th squadron of the 14th Dragoon Little Russian regiment. His diary entries were made in Russian in 1915 on the territory of Belarus. The value of this document lies in the fact that it represents the records made during the hostilities themselves. There is not so much evidence of this kind in Russian historiography. The records allow us to trace the movement of a soldier for more than six months and his perception of military events. Interesting in the diary is a poetic text in the Chuvash language, the author of which is K.D. Efremov, brother of a soldier. The song is filled with philosophical content and was written in the folklore traditions of the Chuvash people.